2020
DOI: 10.1038/s41419-020-2506-0
|View full text |Cite
|
Sign up to set email alerts
|

LINC01116 promotes tumor proliferation and neutrophil recruitment via DDX5-mediated regulation of IL-1β in glioma cell

Abstract: Tumor-associated neutrophils (TANs) are important inflammatory infiltrating cells in the tumor microenvironment and are closely related to the development of human tumor. However, the underlying mechanism of TANs recruiting to glioma remains unknown. Herein, we identified that LINC01116 was significantly upregulated in glioma, and positively correlated with clinical malignancy and survival prognosis. LINC01116 regulated the progression of glioma in vitro and in vivo. RNA-seq analysis demonstrated that LINC0111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…LncRNA genes play important roles in many biological processes. For example, LINC01116 promotes tumor proliferation, migration, and invasion in glioma cell (27,28). However, the role of AC093278.2, AC004067.1, and AC017104.1 in GBM has not been reported, and it is important that it is elucidated in future studies.…”
Section: G Hmentioning
confidence: 99%
“…LncRNA genes play important roles in many biological processes. For example, LINC01116 promotes tumor proliferation, migration, and invasion in glioma cell (27,28). However, the role of AC093278.2, AC004067.1, and AC017104.1 in GBM has not been reported, and it is important that it is elucidated in future studies.…”
Section: G Hmentioning
confidence: 99%
“…Recently, it has been reported that long intergenic nonprotein coding RNA 01116 (LINC01116) promotes nasopharyngeal carcinoma development 9 and accelerates tumor proliferation in glioma. 10 Silencing LINC01116 may inhibit the progression of oral squamous cell carcinoma via microRNA (miR)‐136‐mediated fibronectin 1 (FN1) inhibition. 11 Additionally, LINC01116 has been found to exacerbate lung squamous cell carcinoma progression via targeting the miR‐744‐5p/ sodium voltage‐gated channel beta subunit 1 (SCN1B) axis.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, they reaffirm the need for a multi-targeted approach through a modulation of the TAM. Furthermore, tumor-associated neutrophils (TAN) are found to be involved in necrosis onset in glioblastoma patients [ 105 , 106 ]. In this context, the mechanism of necrosis could be a neutrophil-mediated ferroptosis.…”
Section: Resultsmentioning
confidence: 99%